Family correlates of daughter's and son's locus of control expectancies during childhood. Issue 12 (1st December 2016) - Tully, Erin C.; Gray, Jackson M.; Goodman, Sherryl H.; Nowicki, Stephen
ABSTRACT: Children who expect they can bring about good outcomes and avoid bad outcomes tend to experience more personal successes. Little is known about factors that contribute to these 'control expectancies'. The purpose of the present study was to determine whether children's internal control expectancies occur in the context of parents' internal control expectancies, low family strain, and high family cohesiveness and whether these factors are more strongly related to daughters' than sons' control expectancies. A community sample of 85 children aged 9–11 years and their parents (85 mothers; 63 fathers) completed rating scales. Fathers' more internal control expectancies and mothers' reports of fewer family strains were associated with daughters' but not sons' greater internal control expectancies, and greater family cohesiveness was related to both daughters' and sons' internal control orientations. These findings suggest that family factors may contribute to children's, particularly daughters', development of internal control expectancies.